Insulinotropic action of 2, 4-dinitroanilino-benzoic acid through the attenuation of pancreatic beta-cell lesions in diabetic rats. (1st August 2017) - Jahan, Humera; Choudhary, M. Iqbal; Manzoor, Mehwish; Khan, Khalid Mohammad; Perveen, Shahnaz; Atta-ur-Rahman,
Abstract: Beta cell destruction plays a key role in the pathogenesis of type 1 diabetes mellitus. It has also been argued that beta-cell mass is compromised in some cases of type 2 diabetes, although this is still debated. Currently, the failure of oral antidiabetic insulin secretagogue drugs to properly manage type 2 diabetes demands novel approaches for the treatment of this condition. The aim of the present study was to investigate the in vitro and in vivo antidiabetic effect in STZ-induced diabetic rats, and maximum tolerated dose (MTD) safety of novel anthranilic acid derivative, 2, 4-dinitroanilino-benzoic acid (1 ). Anthranilic acid derivative1 was also evaluated for insulinotropic action on STZ-mediated pancreatic beta-cell lesions in diabetic rats. During an eight week study, oral glucose tolerance test, fasting blood glucose, and serum insulin levels, and pancreatic insulin contents were measured in four different groups of Wistar rats; control, STZ-induced diabetic, gliclazide-treated, and anthranilic acid derivative-treated diabetic rats. Beta-cell number and islet area were also quantified, and immunohistochemical study was performed. In vitro studies in cells showed that 2, 4-dinitroanilino-benzoic acid (1 ) did not adversely effect the cells viability. We found that the derivative1 significantly improved the glucose tolerance, fasting blood glucose, and HbA1c levels, serum insulin levels, and pancreatic insulin contents ( P  < 0.05), comparable to gliclazide-treated group. The derivative1 exhibited a significant insulinotropic action on diabetic pancreas, and caused an increased immunoreactivity for insulin, as compared to gliclazide-treated group. Together these results suggest that treatment of diabetic rats with 2, 4-dinitroanilino-benzoic acid (1 ) improved the glucose tolerance, fasting blood glucose, and HbA1c levels most probably by restoring the functional activities of the pancreas via its insulinotropic action. This indicates that the derivative1 can serve as lead for the treatment of diabetes caused by low insulin levels. Graphical abstract: Highlights: 2, 4-Dinitroanilino-benzoic acid improves glucose metabolism in diabetic rats. 2, 4-Dinitroanilino-benzoic acid restored beta-cell number, and pancreatic insulin contents in diabetic rats. 2, 4-Dinitroanilino-benzoic acid attenuated the STZ-induced atrophy of pancreas of diabetic rats.